The surface rheological signature of the geometric isomers of an azobenzene–surfactant. Issue 18 (26th April 2018) - Hofmann, Matthias J.; Motschmann, Hubert
Abstract : The equilibrium and dynamic surface properties of a photosensitive azobenzene–surfactant subject to illumination with UV and Vis-light leading to the respective geometric cis - and trans -isomers were studied. Abstract : The equilibrium and dynamic surface properties of a photosensitive azobenzene–surfactant subject to illumination with UV and Vis-light leading to the respective geometric cis - and trans -isomers were studied. The adsorption layers formed by the soluble surfactant were characterized by pendant drop tensiometry and surface rheology using the oscillating bubble technique. Aqueous solutions corresponding to the geometric isomers could clearly be distinguished in terms of both their equilibrium and dynamic surface properties. The frequency dependence of the surface dilatational modulus could be described by the extended Lucassen-van den Tempel (LvdT)-model. These findings can be interpreted in terms of the changes of the dipole moment. Furthermore, they shed some light on the relation between the molecular structure and macroscopic properties of the adsorption layer.